The effects of SOD Melon Gliadin as an Antioxidant on VEGF and TGF β blood serum and vitreoretina in hyperglycemia rat model a literature review - Hapsari, Windya Tri; Sasono, Wimbo; Widjaja, Sauli Ari (Edelweiss Applied Science and Technology, 2024)
Diabetes Mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion, action, or both. Persistent hyperglycemia can lead to organ damage, including ocular complications such as diabetic retinopathy. Diabetic retinopathy is a primary cause of preventable blindness and can become vision-threatening if complications are persistent. Over one-third of individuals with diabetes exhibit signs of diabetic retinopathy, and among them, approximately one-third experience vision-threatening diabetic retinopathy (VTDR), defined as severe non-proliferative diabetic retinopathy (NPDR), proliferative diabetic retinopathy (PDR), or the presence of diabetic macular edema (DME). Diabetic retinopathy triggers the production of reactive oxygen species (ROS). Excessive accumulation of ROS can damage tissues surrounding retinal blood vessels, leading to oxidative stress that compromises the blood-retina barrier (BRB). Vascular endothelial growth factor (VEGF) and transforming growth factor-beta (TGF-β) are two markers that indicate retinal dysfunction. Cells possess an intrinsic defense system against ROS, comprising antioxidants such as superoxide dismutase (SOD), glutathione reductase, glutathione peroxidase, and catalase. SOD melon gliadin (Glisodin®) is a potent antioxidant that elevates endogenous SOD levels, reduces ROS, and protects retinal tissues from damage and cell death. Research on SOD melon gliadin (Glisodin®) shows its potential as an antioxidant for preventing diabetic complications in the retina, specifically diabetic retinopathy.